Soil Infiltration Mapping in the Eastern Part of Mijen Sub-District, Semarang City, Indonesia - Dwisaputra Endra; Budianta Wawan; Hendratno Agus (E3S Web of Conferences, 2023)
The increase in population every year will encourage changes in land use from previously green open land to an infrastructure. Changes in land use can alter the condition of existing water infiltration areas. Those changes can cause the land to become impermeable and can increase the potential for surface runoff which can cause floods and landslides. Therefore, a research was carried out on the criticality level of water infiltration areas in the eastern part of Mijen Sub-district, Semarang City with the goal of knowing the criticality level of the water infiltration area and its distribution. This research was conducted by collecting primary data in the form of lithology and soil type by mapping and sampling directly in the field, as well as secondary data in the form of land use and slope which were then verified in the field and analyzed using ArcGIS software. The data collected then analyzed using the Analytical Hierarchy Process (AHP) method by weighing each parameter and subparameter. The parameter used are soil type, land use, slope, and lithology, each of which is divided into several subparameter that will reflect land characteristics. Then the final score for each land characteristic can be calculated from the results of the final weighting of parameters and subparameters. From the final score obtained, all data is then overlaid and classified into several criticality level of water infiltration area to obtain a map of the criticality level of the water infiltration areas. The research area’s criticality level of the water infiltration area can be devided into six condition with it’s distribution, that is good (23,8%), naturally normal (19%), started to be critical (37,4%), slightly critical (6,6%), critical (8,5%), and very critical (4,6%). From the results of this research, it is hoped that it can be a base data and recommendations for maintaining and restoring the criticality of water infiltration areas in the eastern part of Mijen Sub-district.